Optimizing Copper-Aluminum Photovoltaic Cells with Sodium Chloride Gel Electrolyte Under Neon Lamp Ilumination: A Comprehensive Review - Chandra, Dhea Nurfadilla; Mohammad Abdullah; Adhan Efendi; Ilham Saputra (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Photovoltaic cells are devices capable of converting light energy into electrical energy through the photovoltaic effect, where absorbed photons in semiconductor materials generate an electric current. Ideally, photovoltaic cells should offer high efficiency, long-term stability, and low production costs under various lighting conditions. In reality, most conventional photovoltaic technologies, such as crystalline silicon, still suffer from high production costs and performance degradation, especially under long-term exposure and high humidity. As an alternative, copper-aluminum (Cu-Al) based photovoltaic cells with sodium chloride (NaCl) gel electrolyte have been developed, providing reasonable energy conversion efficiency, low material costs, and simple fabrication. The NaCl gel enhances ionic conductivity and system stability, while calcination of Cu into CuO improves the semiconductor properties of the active layer. The urgency of this research lies in the need for renewable energy systems that are affordable, easy to produce, and durable, particularly for remote areas or off-grid applications. Therefore, this article aims to provide a comprehensive review of the optimization of Cu-Al photovoltaic cells with NaCl gel electrolyte under neon lamp illumination, highlighting technical challenges, performance enhancement mechanisms, and future development prospects. This article includes references from publications between 2019 and 2025.